Selecting an intravascular catheter: a modern look and own experience (Perioperaciina Medicina, 2019)
The choice of an intravascular cannula (catheter) is a rather difficult and important issue in modern medicine, especially in the anesthesiology and intensive care unit. In today’s market there are many variants of cannulas, which differ in size and material. As for the size of the cannula, the issue is resolved. The American Medical Device Manufacturers Association proposed measuring the outer diameter of cannulas in “gauge” G. The European Standard ISO 10555.5 regulates the outer diameter of cannulas in millimeters and states that each catheter should have a color marker indicating the nominal outer tube. Color marking helps to find quickly the right size of cannula in extreme situations. The marking of cannulas in “gauge” G and mm is made on the packaging of the product. As to the choice of material, the question remains open. Therefore, in this article, we decided to cover the issue of choice of intravascular cannulas on the material. We have also developed some practical guidelines that facilitate catheterization of peripheral veins and allow cannula to stay longer in the vein. This article will be interesting for doctors and nursing staff.
Keywords: intravascular cannulas; complications; catheter-associated infections; vein choice; selecting aintravascular cannula; polyurethane; teflon (FEP)